Calidad de atención de enfermería en usuarios del Puesto de Salud Chaquinal del cantón Pindal - Elizalde Vera, Elba María (2022)
The quality of nursing care is an important aspect that influences user satisfaction; for this reason, this research was carried out with the objective of analyzing the quality of nursing care in users of the Chaquinal Health Post of the Pindal canton, in order to design an intervention proposal. A descriptive, quantitative and cross-sectional study was carried out; an instrument called CARE-Q was used for data collection, whose internal validity is 0.88 to 0.97, it was composed by 43 questions divided into subscales of nursing behavior, evaluating 6 dimensions: explains and facilitates, comforts, anticipates, maintains a relationship of trust, monitors and follows up. The study population consisted of 48 users aided in the last 6 months. Regarding the results, it was possible to identify that 85.52% of the population surveyed was female, 89.68% between the ages of 20-64 years. Regarding the quality of care provided by the nursing staff, in each of the dimensions evaluated, it was found that the highest percentage of users rated them as good: accessibility (52.08%), explains and facilitates (62.51%), comforts (60.42%), anticipates (45.84%), maintains a relationship of trust (60.43%) and follows up 56.25%. Finally, 56.25% of those surveyed consider that in general the care received by the nursing staff is good, thus, based on the results obtained, an intervention proposal was designed, which will contribute to preserve the quality of nursing care. In conclusion, the quality of care represents an important indicator within health facilities, especially when it is perceived as adequate by patients, since they are the ones who demand services according to their expectations and needs